Bones and cartilage : developmental and evolutionary skeletal biology - Hall, Brian K. (Brian Keith), 1941- (Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
Bones and Cartilage provides the most in-depth review and synthesis assembled on the topic, across all vertebrates. It examines the function, development and evolution of bone and cartilage as tissues, organs and skeletal systems. It describes how bone and cartilage develop in embryos and are maintained in adults, how bone is repaired when we break a leg, or regenerates when a newt grows a new limb, or a lizard a new tail. The second edition of Bones and Cartilage includes the most recent knowledge of molecular, cellular, developmental and evolutionary processes, which are i.